Current and future vulnerability of South African ecosystems to perennial grass invasion under global change scenarios - Rahlao, Sabataolo John (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Conservation Ecology and Entomology))--University of Stellenbosch, 2010.